Vulnerability of Cyber Security Is an Unexpected Threat to Global Internet System - Mohajan, Haradhan Kumar (Art and Society, 2025)
At present the world is becoming highly interconnected, and cyber security is essential for the sustainability and development of the global networking. Cyber security is the practice of protecting digital devices, networks, and sensitive data from cyber threats, such as hacking, malware, and phishing attacks that are committed over the internet by technically skilled criminals, who have a wide range of strategies, technologies, and best practices. It is an urgent national and global problem. At present it becomes an incredibly complex and changing policy and important issue in the infrastructure of every company and organization. Data in computer can be lost or destroyed through physical and natural disasters, such as floods, fires, and unexpected catastrophes done by the cyber criminals. The purpose of this study is to discuss the aspects of cyber security for the improvement of the safety and security of cyber space.